Presentation of the Citizens’ administrative law circle - Nikolova, Raina (Law Journal of New Bulgarian University, 2022)
The paper presents the two main topics discussed with the participants of the Administrative Law of Citizens Circle during the spring semester of the academic year 2021/2022: the administrative legal status of refugees and the administrative military law and the rights of citizens.